2002
DOI: 10.1002/path.1153
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoietic stem cells1

Abstract: Considerable efforts have been made in recent years in determining the composition of the cell types that constitute the human haematopoietic stem cell (HSC) compartment. These studies have emphasized the heterogeneity of the human HSC in terms of proliferative and self-renewal capacities. Recent studies have indicated that CD34 is not the universal marker of all human HSCs. New markers for purifying HSCs have been described. A number of genes that regulate the formation, self-renewal, or differentiation of HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 146 publications
(153 reference statements)
0
71
0
3
Order By: Relevance
“…CD34 has been long believed to be an HSC marker, but recent data revealed that the expression of CD34 is reversible and regulated by HSC activation. 22,23 Although the functional significance of CD34 remains unclear, L-selectin on leukocytes and E-selectin on vascular endothelium are putative ligands of CD34. [36][37][38] Our preliminary data showed both the CD34 þ and CD34 À fractions of SUG cells could similarly reconstitute leukemia in NOG mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD34 has been long believed to be an HSC marker, but recent data revealed that the expression of CD34 is reversible and regulated by HSC activation. 22,23 Although the functional significance of CD34 remains unclear, L-selectin on leukocytes and E-selectin on vascular endothelium are putative ligands of CD34. [36][37][38] Our preliminary data showed both the CD34 þ and CD34 À fractions of SUG cells could similarly reconstitute leukemia in NOG mice.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Intravenous injection of human leukemia cells into non-obese diabetes/severe combined immunodeficiency (NOD/SCID) mice, which is now the most common and most nearly physiological method to identify human HSCs in vivo, shows that leukemia cells expressing primitive cell surface makers such as CD34 þ and CD38 À can repopulate NOD/SCID mice regardless of the acute myeloid leukemia (AML) type. [21][22][23] The concept of leukemia stem cells (LSCs) may change current notions about how leukemia develops and how leukemia should be treated. However, the microenvironment for LSC is not yet well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental studies challenging the extensive plasticity of stem cells will not be described here in detail, because they have been the subject of many excellent reviews (Verfaille, 2002;Bonnet, 2003;Vassilopoulos et al, 2003;Moore and Quesenberry, 2003;Pauwelyn and Verfaillie, 2006;Stocum, 2006). In general, these studies and their accompanying review articles have provided several alternative explanations for the apparent plasticity of transplanted stem cells (Fig.…”
Section: Mammalian Stem Cell Plasticity: Real or Just Wishful Thinkingmentioning
confidence: 99%
“…326 This model and those following in the remainder of this section have been used extensively to study normal human haematopoiesis, but for the purposes of this review the authors will focus only on human AML xenografts and refer the reader to some excellent reviews for the latter. [327][328][329][330][331][332][333] The first successful report of human stem cell engraftment into a scid mouse was reported in 1988 316 following transplantation of human foetal tissues with subsequent engraftment of hu-AML into scid recipients in 1991. 334 Consequent studies 280,[334][335][336][337][338][339][340][341][342] resulted in the inchoate identification of the CD34 þ CD38 À scid leukaemia initiating cell (SL-IC) 335,343 whose phenotype is similar to normal HSCs, and the finding that AMLs of differing FAB classifications which engrafted in scid recipients faithfully recapitulated their intrinsic pathological and clinically observed disparities.…”
Section: Nude Modelsmentioning
confidence: 99%